Glycosphingolipid synthesis requires FAPP2 transfer of glucosylceramide. - D'Angelo, G; Polishchuk, E; Di Tullio, G; Santoro, M; Di Campli, A; Godi, A; West, G; Bielawski, J; Chuang, C; van der Spoel, A; Platt, F; Hannun, Y; et al. (2007)
The molecular machinery responsible for the generation of transport carriers moving from the Golgi complex to the plasma membrane relies on a tight interplay between proteins and lipids. Among the lipid-binding proteins of this machinery, we previously identified the four-phosphate adaptor protein FAPP2, the pleckstrin homology domain of which binds phosphatidylinositol 4-phosphate and the small GTPase ARF1. FAPP2 also possesses a glycolipid-transfer-protein homology domain. Here we show that human FAPP2 is a glucosylceramide-transfer protein that has a pivotal role in the synthesis of complex glycosphingolipids, key structural and signalling components of the plasma membrane. The requirement for FAPP2 makes the whole glycosphingolipid synthetic pathway sensitive to regulation by phosphatidylinositol 4-phosphate and ARF1. Thus, by coupling the synthesis of glycosphingolipids with their export to the cell surface, FAPP2 emerges as crucial in determining the lipid identity and composition of the plasma membrane.